2017
DOI: 10.3390/rs9111149
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In-Season Cotton Nitrogen Status and Lint Yield Prediction from Unmanned Aerial System Imagery

Abstract: Abstract:The present work assessed the usefulness of a set of spectral indices obtained from an unmanned aerial system (UAS) for tracking spatial and temporal variability of nitrogen (N) status as well as for predicting lint yield in a commercial cotton (Gossypium hirsutum L.) farm. Organic, inorganic and a combination of both types of fertilizers were used to provide a range of eight N rates from 0 to 340 kg N ha −1 . Multi-spectral images (reflectance in the blue, green, red, red edge and near infrared bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 31 publications
10
42
1
Order By: Relevance
“…The CCCI has been reported to correlate well with plant N in wheat and durum wheat (Bronson et al., 2017a; Cammarano et al., 2011) and in cotton (Barnes et al., 2000). Recent reports with cotton indicated that CCCI performed as well as (Ballester et al., 2017) or better than NDRE (Raper & Varco, 2015) in estimating cotton N status in the field. Raper and Varco (2015) state that CCCI standardizes for biomass and would be effective for early‐season N assessment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The CCCI has been reported to correlate well with plant N in wheat and durum wheat (Bronson et al., 2017a; Cammarano et al., 2011) and in cotton (Barnes et al., 2000). Recent reports with cotton indicated that CCCI performed as well as (Ballester et al., 2017) or better than NDRE (Raper & Varco, 2015) in estimating cotton N status in the field. Raper and Varco (2015) state that CCCI standardizes for biomass and would be effective for early‐season N assessment.…”
Section: Discussionmentioning
confidence: 97%
“…The NDRE is not nearly as well‐studied in the literature as the NDVI, but its use in agricultural research is increasing (Ballester, Hornbuckle, Brinkhoff, Smith, & Quayle, 2017; Barnes et al., 2000; Bean et al., 2018; Long et al., 2009; Montealegre, Wortman, Fergusan, Shaver, & Schepers, 2019; Raper & Varco, 2015; Shiratsuchi et al., 2011; Stamatiadis et al., 2019). Shiratsuchi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation biomass [22,103] nitrogen status [22,99,103,110] moisture content [109,110] vegetation color [49,54] spectral behavior of chlorophyll [64,99] temperature [64,69] spatial position of an object [32,106] size and shape of different elements and plants vegetation indices [54][55][56] Soil moisture content [109,112] temperature [66,69] electrical conductivity [66] With the use of specialized sensors, UAVs can acquire information for various features of the cultivated field. However, as mentioned above, there is still no standardized workflow or well established techniques to follow for analyzing and visualizing the information acquired.…”
Section: Crop Featuresmentioning
confidence: 99%
“…Regression has been used to estimate spectral vegetation indices by analyzing data acquired from RGB images [35], presenting generally good results. Additionally, regression has been used to examine the correlation of some vegetation indices with vegetation features such as nitrogen [22,38,99], leaf are index [36,103], and biomass [22,36,103]. For this purpose, both linear (simple and multiple) regression and nonlinear regression methods have been used.…”
Section: Using Machine Learningmentioning
confidence: 99%